KINERJA PENDIDIKAN ANAK USIA DINI (PAUD) DI KECAMATAN PARIGI BARAT KABUPATEN PARIGI MOUTONG - Frelly, Deasy Mona (Katalogis, 2016)
This research was conducted to analyze the performance of Early Childhood Education in Parigi Barat Sub-district, Parigi Moutong Regency the involved informants in this research are the teachers of TK Satu Atap Baliara, the principle of TK Al-Khairaat Kayuboko, the principle of TK Satu Atap Parigimpu'u, the kindergartens supervisor and Unit Head of Technical Executive of Parigi Barat Sub-district, the data collection techniques are observations, interviews and documentations, the data used is primary data obtained directly from the informants who were then analyzed by the stages of data reduction, presentation and conclusion, the type of this research is Qualitative descriptive which uses Agus Dwiyanto's performance theory. Based on the results of this research, it is found a difference between the ideal values and the reality, so it is concluded that the performance of Early Childhood Education is not optimal, it is proven by a test in the aspect of productivity related to the presence of teachers in schools and classrooms, the aspect of service quality withÂ learning implementation indicator, the aspect of responsiveness is seen from the approach used by the teachers in learning either the method or the use of media, accountability aspect is seen from the work ethic and responsibility are not well implemented, the only aspect which is implemented well is the responsibility as measured from the involvement of teachers in developing the curriculum and preparing teaching materials.